2010
DOI: 10.1007/s00247-010-1581-2
|View full text |Cite
|
Sign up to set email alerts
|

Use and accuracy of US guidance for image-guided injections of the temporomandibular joints in children with arthritis

Abstract: In our experience, TMJ injections using sonographic guidance is a safe, effective and accurate procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0
2

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 13 publications
4
39
0
2
Order By: Relevance
“…The present findings confirm previous reports that IACI of the TMJ can be safely performed in children with JIA [10][11][12][13]16 ; moreover, this is the first study to report that the procedure can be performed with MAC in the absence of imaging guidance. This is important for 2 reasons.…”
Section: Discussionsupporting
confidence: 93%
“…The present findings confirm previous reports that IACI of the TMJ can be safely performed in children with JIA [10][11][12][13]16 ; moreover, this is the first study to report that the procedure can be performed with MAC in the absence of imaging guidance. This is important for 2 reasons.…”
Section: Discussionsupporting
confidence: 93%
“…This procedure is performed routinely in many centers, reporting excellent clinical results and a very low complication rate. 31,76 There is, however, a concern that the current level of evidence allows only very limited conclusions on the effect of steroid injections in JIA patients with TMJ arthritis as shown in a systematic review on efficacy and safety. 78 Moreover, experimental animal studies do not indicate a positive effect on the mandibular growth by the use of steroid injection in the TMJ as an early treatment of inflammation.…”
Section: Image-guided Treatment Of Tmj Arthritismentioning
confidence: 97%
“…[14] Other studies also confirmed that corticosteroid injection of the TMJ can be safely performed in children with JIA, and is effective. [15][16][17][18] Few studies have evaluated TMJ corticosteroid injection in JIA. In these studies the volume of corticosteroid injected was chosen empirically.…”
Section: Temporomandibular Disorders (Tmds)mentioning
confidence: 99%